ANALYSIS OF FINANCIAL RATIO ON FINANCIAL DISTRESS IN CONSUMER CYCLICAL SECTOR COMPANIES - Junaidi, M. Hilmi; Widajantie, Tituk Diah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2023)
This study aims to analyze the effect of financial ratios on financial distress during the Covid-19 pandemic. The research method used is quantitative analysis. The data used is secondary data in the form of annual reports of consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX) for three years from 2019 to 2021. The sample for this study was 27 companies that experienced losses twice in the research period. The sampling technique is purposive sampling. Data analysis techniques in this study consisted of multiple linear regression analysis, classical assumptions, hypothesis testing (t-test and F-test), and coefficient of determination test. The study results show that the ratio of liquidity, leverage, profitability, and activity simultaneously affects predicting financial distress. Partially, leverage, profitability, and activity ratios have a positive and significant effect. In contrast, the liquidity ratio does not affect the possibility of financial distress in consumer cyclical sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021